Strategi Pembelajaran Pendidikan Anak Usia Dini di Masa Pandemi Covid-19 - Suhendro, Eko (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2020)
The existence of COVID 19 which still hit Indonesia until September had a negative impact on education in Indonesia, especially early childhood education. This makes learning, which was a face-to-face system, must be changed to distance education. In order for learning to continue optimally, of course, the teacher must be able to apply different learning strategies. The type of research used is qualitative descriptive which is used to obtain safe information and from the effects of the COVID-19 pandemic on teaching and learning activities in PAUD. Research subjects / respondents for this study were teachers and parents of students who followed the PAUD Engineering level, data in the form of interviews. The application of learning strategies carried out by teachers during the Covid pandemic is by learning at home with online and offline methods. Bold learning is carried out through online networks such as through WA Groups as well as text messages and telephone. In addition, using other media such as television shows. While offline learning is carried out through the home visit method. Implementation of house-to-house learning is expected so that students get direct learning material to cover learning deficiencies who dare to experience some disturbances. The results of this study will be useful as a reference for PAUD teachers who have implemented learning during the COVID-19 pandemic.